1998
DOI: 10.1159/000006577
|View full text |Cite
|
Sign up to set email alerts
|

Different Brain Morphologies from Different Genotypes in a Single Teleost Species, the Medaka <i>(Oryzias latipes)</i>

Abstract: In a teleost fish, the medaka (Oryzias latipes), many inbred strains have been established from various origins including wild populations. Brains from five genetically different strains, which had been bred and raised under the same conditions, were examined to determine whether there is intraspecific genetic variation. A total of 25 brains from the wild-type strains (HNI-II, HB11A and HB32C) and from the body-colour mutant strains (Hi3 and HO5) were fixed, and the external features of the brains were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 23 publications
1
38
0
4
Order By: Relevance
“…Notably, the comparison between chick inbred lines demonstrated that DMRs responsible for differences in immune response reside in gene bodies as well as promoters . Taken together, although about 13 or 23% of the HMDs are unmapped in each species, the species-specific HMDs most likely confer species-specific morphological and physiological characters in medaka species (Ishikawa et al, 1999;Kimura et al, 2007;Asai et al, 2011;Tsuboko et al, 2014) and thus will be interesting targets for the future study of speciation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the comparison between chick inbred lines demonstrated that DMRs responsible for differences in immune response reside in gene bodies as well as promoters . Taken together, although about 13 or 23% of the HMDs are unmapped in each species, the species-specific HMDs most likely confer species-specific morphological and physiological characters in medaka species (Ishikawa et al, 1999;Kimura et al, 2007;Asai et al, 2011;Tsuboko et al, 2014) and thus will be interesting targets for the future study of speciation.…”
Section: Discussionmentioning
confidence: 99%
“…Inbred strains of medaka differ in terms of various quantitative traits, including body shape, behavior, and susceptibility to chemical or radiation-induced tumorigenesis (Hyodo-Taguchi 1990). Furthermore, gross brain morphology varies greatly in five inbred strains with different genotypes (Ishikawa et al 1999). The availability of a dense and accurate genetic linkage map (Naruse et al 2004b;Kimura et al 2005), in combination with a number of inbred strains that display diverse quantitative traits, makes it possible to identify QTL for complex traits in the medaka.…”
mentioning
confidence: 99%
“…It has been reported that the morphology of the brain is different for different genotypes of medaka [11], but the studies were done by first anaesthetizing the fish and then fixing the brain in a fixative solution such as para-formaldehyde and observing it through a stereomicroscope. Morphogenesis of optic tectum and cerebellum were studied separately using histology, where various stages and patterns in the development process were identified [12,33].…”
Section: Discussion -Brainmentioning
confidence: 99%
“…Ishikawa et al have shown that brain morphology is different for different species of medaka [11] with a specific strain having a larger optic tectum and smaller telencephalon compared to other strains. Morphogenesis of optic tectum [11] and cerebellum [12] has been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation